The development of society and the principle of "minimizing efforts"/"acceptable crisis". - Suschiy, Sergey Yakovlevich (SHS Web of Conferences, 2023)
The paper analyses the reasons for obvious resource saving and minimization of practical efforts made by society in the solution of significant problems that arise in the process of its development. This phenomenon is recorded in the life of societies of all taxonomic levels (from local groups to states, international unions, humanity in general). It can be referred to as the principle of "effort minimization". The main reasons for the use of this principle by society in its activities are the limited availability of resources, which implies a concentration of efforts on stopping the clip of central threats, as well as the ability of social subsystems in the development process in order to solve some problems without the regulatory involvement of management structures. For the global society, another significant reason is the maximum difficulty in the coordination of the efforts of a large number of actors. While there are significant differences in the methods, strategies and tools used by societies to remove threats, the very mechanism of response to them has several common features, similar stages ("blindness", fixation, practical efforts, effective activity). Minimizing regulatory actions for a long time, society actually contributes to the growth of some problems, deliberately allowing the onset of a crisis situation, with its subsequent regulation (the principle of "acceptable crisis"). It is possible to state that the development of civilization is fundamentally located in the risk zone. Moreover, such riskogenicity is the manifestation of a systemic algorithm responsible for the way of evolution not only of humanity, but of the entire biosphere. It does not secure against a catastrophic outcome (evidence is the disappearance of species and large "clusters" of living things; local societies, states, peoples, entire civilizations). At the same time, the growth of global risks correlates with the expansion of social ability to eliminate them. It remains to be hoped for the width of the time gap between the achievement of a critical level of actualization by global issues (forcing society to actively engage in the process of self-optimization) and the onset of catastrophic changes in the socio-natural system of the Earth, when any regulatory actions on the part of mankind will be useless.